Strengthening The Pancasila Student Profile In The Independent Curriculum at Elementary Schools - Melyani Sari Sitepu; Baihaqi Siddik Lubis; Ryan Taufika (Lembaga Bale Literasi, 2026)
The Pancasila Student Profile is one of the government's efforts to internalize Pancasila values ??in society through education. This study was conducted to analyze the implementation of the Pancasila student profile in the independent curriculum, especially in differentiated learning methods in Elementary Schools. The purpose of this study is to describe the application of the Pancasila student profile in the independent curriculum for students of UPT SD Negeri 17 Durian, Medang Deras District, using the Pancasila student profile dimension indicators. This study uses a qualitative method with a descriptive approach. The research subjects were the principal, the fourth-grade homeroom teacher, and fourth-grade students of SD Negeri 17 Durian. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed using data triangulation techniques. The results of the study show that the implementation of the independent curriculum is effective in shaping students' character. Most students are in the good category in the dimensions of faith and noble character (68%), global diversity (46.6%), cooperation (31.6%), independence (96%), creativity (21.6%), and critical reasoning (47.97%). Implementing this curriculum not only increases students' motivation and potential but also shapes their character, developing them into intelligent and disciplined individuals. These results imply that the independent curriculum can shape the Pancasila Student Profile.